A clinical prediction model based on interpretable machine learning algorithms for prolonged hospital stay in acute ischemic stroke patients: a real-world study - Wang, Kai; Jiang, Qianmei; Gao, Murong; Wei, Xiu’e; Xu, Chan; Yin, Chengliang; Liu, Haiyan; Gu, Renjun; Wang, Haosheng; Li, Wenle; Rong, Liangqun (Frontiers in Endocrinology, 2023)
Abstract Objective: Acute ischemic stroke (AIS) brings an increasingly heavier economic burden nowadays. Prolonged length of stay (LOS) is a vital factor in healthcare expenditures. The aim of this study was to predict prolonged LOS in AIS patients based on an interpretable machine learning algorithm. Methods: We enrolled AIS patients in our hospital from August 2017 to July 2019. Patients who had a length of stay greater than 7 days were divided into the "prolonged LOS" group. The least absolute shrinkage and selection operator (LASSO) regression was applied to reduce the dimensionality of the data. We compared the predictive capacity of extended LOS in eight different machine-learning algorithms. Shapley additive explanations (SHAP) values were used to interpret the outcome, and the most optimal model was assessed by discrimination, calibration, and clinical utility. Results: Prolonged LOS developed in 149 (22.0%) of the 677 eligible patients. In eight machine-learning algorithms, prolonged LOS was best predicted by the Gaussian NB (GNB) model, which had a striking area under the curve (AUC) of 0.878±0.007 in the training set and 0.857±0.039 in the validation set. The variables sorted by the gap values showed the strongest predictors were pneumonia, dysphagia, thrombectomy, and stroke severity. High net benefits were observed at 0–76% threshold probabilities, while good agreement was found between the observed and predicted probabilities. Conclusions: The model using the GNB algorithm proved excellent for predicting prolonged LOS in AIS patients. This simple model of prolonged hospitalization could help adjust policies and better utilize resources.